Gumdrop to the rescue - Biro, Val (London : Puffin Books, 1986)
Gumdrop, the best loved motor car in the world, celebrates his 60th birthday by travelling down to the Historic Motor Show at Beaulieu. On the way, the vintage AA motorbike is stolen.
Keywords: Car -- Fiction; Children stories